A Content Analysis of Readers' Comments on Political and Economic News Articles from Zimbabwe Online Media. (2nd January 2017) - Mathe, Limukani; Caldwell, Marc
ABSTRACT: Web 2.0 technologies have promoted media audience interaction and participation, which was beforehand limited to traditional media through the letters that were sent to the editor and radio conversations. This paper studies the media audiences found on readers' public commentary forums attached to political and economic news articles. The paper implements a qualitative content analysis to analyze readers' perspectives on the political and economic situation in Zimbabwe by extracting comments found on NewZimbabwe.com, Herald.co.zw, Nehandaradio.com and Zimeye.com . This paper reveals that the perspectives of readers on political and economic issues are extremely contrary influenced by political or media polarization. The paper shows that readers' divergent views on the political economy are distributed amid the political opinions and roles played by either ZANU-PF or MDC.